2020
DOI: 10.1080/14756366.2020.1780227
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and biological characterisation of novelN5-substituted paullones targeting the biosynthesis of trypanothione inLeishmania

Abstract: Trypanothione synthetase (TryS) produces N 1 ,N 8-bis(glutathionyl)spermidine (or trypanothione) at the expense of ATP. Trypanothione is a metabolite unique and essential for survival and drug-resistance of trypanosomatid parasites. In this study, we report the mechanistic and biological characterisation of optimised N 5-substituted paullone analogues with anti-TryS activity. Several of the new derivatives retained submicromolar IC 50 against leishmanial TryS. The binding mode to TryS of the most potent paullo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(55 citation statements)
references
References 50 publications
(105 reference statements)
3
46
0
2
Order By: Relevance
“…In both cases, the new analogues retained their on-target effect against the pathogen as confirmed by genetic 9 or metabolic approaches 13 . Kinetic, thermodynamic and computational approaches suggested that paullones occupy the polyamine and second glutathione binding site of TryS 13 . Yet, the identification of multi-spectrum TryS inhibitors with reasonable biological activity and selectivity proved unsuccessful.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…In both cases, the new analogues retained their on-target effect against the pathogen as confirmed by genetic 9 or metabolic approaches 13 . Kinetic, thermodynamic and computational approaches suggested that paullones occupy the polyamine and second glutathione binding site of TryS 13 . Yet, the identification of multi-spectrum TryS inhibitors with reasonable biological activity and selectivity proved unsuccessful.…”
Section: Introductionmentioning
confidence: 71%
“…Inhibition of trypanothione synthesis either by genetic 6 , 7 or chemical 9 , 12 , 13 approaches leads to an intracellular oxidative milieu due to exhaustion of the antioxidant system to cope with the elimination of endogenous peroxides caused by trypanothione depletion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound VI showed superior activity with IC 50 0.3 μM against Li TryS , thus inhibiting L. braziliensis (EC 50 0.2-0.4 μM) and L. infantum (EC 50 0.9 � 0.1 μM) amastigotes with good selectivity index. [18] Choi et al, isolated Marinoazepinone B and demonstrated a 16 mm zone of inhibition against the Pontibacillus sp. [19] Arora et al, reported multi-step synthesis of new Quinolino annulated azepinones (VIII) and its antibacterial properties against E. coli with MIC 1 μg/mL.…”
Section: Introductionmentioning
confidence: 99%